Isatuximab plus pomalidomide and low-dose dexamethasone versus pomalidomide and low-dose dexamethasone in patients with relapsed and refractory multiple myeloma (ICARIA-MM): a randomised, multicentre, open-label, phase 3 study - Attal, Michel; Richardson, Paul G; Rajkumar, S Vincent; San-Miguel, Jesus; Beksac, Meral; Spicka, Ivan; Leleu, Xavier; Schjesvold, Fredrik; Moreau, Philippe; Dimopoulos, Meletios A; Huang, Jeffrey Shang-Yi; Minarik, Jiri; et al. (Lancet, 2019)
BACKGROUND: Isatuximab is a monoclonal antibody that binds a specific epitope on the human CD38 receptor and has antitumour activity via multiple mechanisms of action. In a previous phase 1b study, around 65% of patients with relapsed and refractory multiple myeloma achieved an overall response with a combination of isatuximab with pomalidomide and low-dose dexamethasone. The aim of this study was to determine the progression-free survival benefit of isatuximab plus pomalidomide and dexamethasone compared with pomalidomide and dexamethasone in patients with relapsed and refractory multiple myeloma. METHODS: We did a randomised, multicentre, open-label, phase 3 study at 102 hospitals in 24 countries in Europe, North America, and the Asia-Pacific regions. Eligible participants were adult patients with relapsed and refractory multiple myeloma who had received at least two previous lines of treatment, including lenalidomide and a proteasome inhibitor. Patients were excluded if they were refractory to previous treatment with an anti-CD38 monoclonal antibody. We randomly assigned patients (1:1) to either isatuximab 10 mg/kg plus pomalidomide 4 mg plus dexamethasone 40 mg (20 mg for patients aged ≥75 years), or pomalidomide 4 mg plus dexamethasone 40 mg. Randomisation was done using interactive response technology and stratified according to the number of previous lines of treatment (2-3 vs >3) and age (<75 years vs ≥75 years). Treatments were assigned based on a permuted blocked randomisation scheme with a block size of four. The isatuximab-pomalidomide-dexamethasone group received isatuximab intravenously on days 1, 8, 15, and 22 in the first 28-day cycle, then on days 1 and 15 in subsequent cycles. Both groups received oral pomalidomide on days 1 to 21 in each cycle, and oral or intravenous dexamethasone on days 1, 8, 15, and 22 of each cycle. Treatment continued until disease progression, unacceptable toxicity, or consent withdrawal. Dose reductions for adverse reactions were permitted for pomalidomide and dexamethasone, but not for isatuximab. The primary endpoint was progression-free survival, determined by an independent response committee and assessed in the intention-to-treat population. Safety was assessed in all participants who received at least one dose of study drug. This study is registered at ClinicalTrials.gov, number NCT02990338. FINDINGS: Between Jan 10, 2017, and Feb 2, 2018, we randomly assigned 307 patients to treatment: 154 to isatuximab-pomalidomide-dexamethasone, and 153 to pomalidomide-dexamethasone. At a median follow-up of 11·6 months (IQR 10·1-13·9), median progression-free survival was 11·5 months (95% CI 8·9-13·9) in the isatuximab-pomalidomide-dexamethasone group versus 6·5 months (4·5-8·3) in the pomalidomide-dexamethasone group; hazard ratio 0·596, 95% CI 0·44-0·81; p=0·001 by stratified log-rank test. The most frequent treatment-emergent adverse events (any grade; isatuximab-pomalidomide-dexamethasone vs pomalidomide-dexamethasone) were infusion reactions (56 [38%] vs 0), upper respiratory tract infections (43 [28%] vs 26 [17%]), and diarrhoea (39 [26%] vs 29 [20%]). Adverse events with a fatal outcome were reported in 12 patients (8%) in the isatuximab-pomalidomide-dexamethasone group and 14 (9%) in the pomalidomide-dexamethasone group. Deaths due to treatment-related adverse events were reported for one patient (<1%) in the isatuximab-pomalidomide-dexamethasone group (sepsis) and two (1%) in the pomalidomide-dexamethasone group (pneumonia and urinary tract infection). INTERPRETATION: The addition of isatuximab to pomalidomide-dexamethasone significantly improves progression-free survival in patients with relapsed and refractory multiple myeloma. Isatuximab is an important new treatment option for the management of relapsed and refractory myeloma, particularly for patients who become refractory to lenalidomide and a proteasome inhibitor. FUNDING: Sanofi. VIDEO ABSTRACT.
Keywords: doba přežití bez progrese choroby; Antibodies, Monoclonal; mužské pohlaví; Male; senioři; výsledek terapie; Thalidomide; Female; Humans; Multiple Myeloma; lokální recidiva nádoru; lidé; Severní Amerika; Middle Aged; ženské pohlaví; lidé středního věku; Evropa; mnohočetný myelom; Antineoplastic Combined Chemotherapy Protocols; thalidomid; monoklonální protilátky; Progression-Free Survival; Asie; Treatment Outcome; protokoly protinádorové kombinované chemoterapie; Europe; dexamethason; North America; Dexamethasone; Neoplasm Recurrence, Local; Aged; Asia